IMPACT OF ACQUIRED DYSARTHRIA ON SPEECH PARAMETERS AND MENTAL HEALTH IN PATIENTS WITH NEUROLOGICAL DISORDERS: A COHORT STUDY IN PAKISTAN (The Research of Medical Science Review, 2025)
This study analyzed the impact of acquired dysarthria on various speech parameters and mental health in patients with multiple neurological disorders. Seventy-eight participants were assessed, categorized by demographics such as age, gender, marital status, occupation, and family medical history. Chi-square tests were employed to examine associations between these demographic factors and medical conditions, revealing a high prevalence of hypertension, hearing impairment, and stroke. Additionally, 40% of participants reported a family history of medical conditions, suggesting possible hereditary influences. The study specifically evaluated speech parameters, including respiration, phonation, facial musculature, articulation, diadochokinesis, reflexes, and prosody, in patients diagnosed with dysarthria. ANOVA tests were conducted to distinguish between groups with "Good" and "Poor" speech abilities. Results indicated that diadochokinesis and prosody showed statistically significant differences (p < 0.001) between these groups, while articulation and facial musculature also showed notable differences. Anxiety and depression levels were assessed using the Hospital Anxiety and Depression Scale (HADS), revealing a significant association between higher anxiety and depression levels and dysarthric features. The findings indicate that diadochokinesis and prosody are key distinguishing parameters among dysarthric patients, underscoring their importance in targeted therapeutic interventions. These insights contribute to understanding the interplay between dysarthria, speech abilities, and mental health in neurological disorders, providing a foundation for developing effective rehabilitation strategies to improve patient outcomes.